Model Pemberdayaan Kader untuk Keberlanjutan Intervensi Gizi - Wahyutri, Endah; Ratnawati, Ratnawati; Hilda, Hilda; Putri, Rosalin Ariefah; Hairiyah, Saibatul (Universitas Muhammadiyah Mataram, 2026)
Abstract: This activity aimed to evaluate the effectiveness of a structured cadre empowerment model in enhancing Posyandu cadres' capacity (knowledge, attitude, and practice readiness) for providing supplementary feeding based on local food sources at Mangkupalas Community Health Center, Samarinda City. This participatory empowerment activity involved 55 Posyandu cadres over two months, utilizing training, demonstration, mentoring, and supervision. Evaluation was conducted solely by measuring changes in cadre knowledge and attitude using pre- and post-tests. The program demonstrated significant success in human resource development. The average knowledge score of the cadres increased from 91.6 to 94.0, and the percentage of cadres showing good attitudes increased significantly from 65% to 91%. Conclusion: The cadre empowerment model proved highly effective in improving cadre knowledge and motivation, establishing a strong foundation for the sustained implementation and effectiveness of local food-based PMT programs at the community level.Abstrak: Kegiatan ini bertujuan mengevaluasi efektivitas model pemberdayaan kader terstruktur dalam meningkatkan kapasitas kader Posyandu untuk memberikan makanan tambahan (PMT) berbasis pangan lokal di Puskesmas Mangkupalas, Kota Samarinda. Aktivitas pemberdayaan partisipatif ini melibatkan 55 kader Posyandu melalui pelatihan, demonstrasi, pendampingan, dan supervisi selama dua bulan. Evaluasi dilakukan dengan mengukur perubahan pengetahuan dan sikap kader melalui pre/post-test. Program ini menunjukkan keberhasilan signifikan. Rata-rata nilai pengetahuan kader meningkat dari 91,6 menjadi 94,0, dan persentase kader dengan sikap baik meningkat dari 65% menjadi 91%. Peningkatan ini memvalidasi efektivitas pelatihan dalam pengembangan sumber daya manusia lokal.